Ritual murder in Russia, Eastern Europe, and beyond : new histories of an old accusation - Avrutin, Eugene M.; Dekel-Chen, Jonathan L.; Weinberg, Robert (Bloomington, Indiana : Indiana University Press, 2017)
This innovative reassessment of ritual murder accusations brings together scholars working in history, folklore, ethnography, and literature. Favoring dynamic explanations of the mechanisms, evolution, popular appeal, and responses to the blood libel, the essays rigorously engage with the larger social and cultural worlds that made these phenomena possible. In doing so, the book helps to explain why blood libel accusations continued to spread in Europe even after modernization seemingly made them obsolete. Drawing on untapped and unconventional historical sources, the collection explores a range of intriguing topics: popular belief and scientific knowledge; the connections between antisemitism, prejudice, and violence; the rule of law versus the power of rumors; the politics of memory; and humanitarian intervention on a global scale.--Publisher's description.
7 Human Sacrifice in the Name of a Nation: The Religion of Common Blood8 The Predatory Jew and Russian Vitalism: Dostoevsky, Rozanov, and Babel; 9 Connecting the Dots: Jewish Mysticism, Ritual Murder, and the Trial of Mendel Beilis; 10 A Half-Full Cup? Transnational Responses to the Beilis Affair; 11 Simulating Justice: The Blood Libel Case in Moscow, April 1922; 12 The Blood Libel and Its Wartime Permutations: Cannibalism in Soviet Lviv; 13 Was the Doctors' Plot a Blood Libel?; 14 The Sandomierz Paintings of Ritual Murder as Lieux de mémoire; Index.
"The collection emerged out of a conference at the University of Illinois in October 2014"--Acknowledgments.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on July 13, 2017).
JSTOR
Keywords: Blood accusation -- Russia -- History -- Congresses; Blood accusation -- Europe, Eastern -- History -- Congresses; Jews -- Persecutions -- Russia -- History -- Congresses; Jews -- Persecutions -- Europe, Eastern -- History -- Congresses; Antisemitism -- Russia -- History -- Congresses; Antisemitism -- Europe, Eastern -- History -- Congresses; Russia -- Ethnic relations -- Congresses; Europe, Eastern -- Ethnic relations -- Congresses; Meurtre rituel -- Russie -- Histoire -- Congrès.; Meurtre rituel -- Europe de l'Est -- Histoire -- Congrès.; Juifs -- Persécutions -- Russie -- Histoire -- Congrès.; Juifs -- Persécutions -- Europe de l'Est -- Histoire -- Congrès.; Antisémitisme -- Russie -- Histoire -- Congrès.; Antisémitisme -- Europe de l'Est -- Histoire -- Congrès.; Europe de l'Est -- Relations interethniques -- Congrès.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Europe -- Eastern; Antisemitism; Blood accusation; Ethnic relations; Jews -- Persecutions; Eastern Europe; Russia; Conference papers and proceedings; History